A new aqueous all-organic flow battery with high cell voltage in acidic electrolytes. (15th January 2021) - Leung, P.; Martin, T.; Xu, Q.; Flox, C.; Mohamad, M.R.; Palma, J.; Rodchanarowan, A.; Zhu, X.; Xing, W.W.; Shah, A.A.
Graphical abstract: Highlights: New all-organic redox flow battery based on acidic aqueous electrolytes. New fundamental understanding of potential molecules in acids. Multi electron-proton transfer and highest cell voltage reported to date. High energy efficiency and capacity retention during cycling. Abstract: To ensure deeper market penetration, electrolytes of redox flow batteries (RFB) should be based on low-cost and abundant materials. An all-organic system based on acidic aqueous electrolytes is developed, from a study of theoretical calculations, fundamental chemistry to full-cell testing. The selection of organic active materials in relation to their physical and chemical properties (reaction kinetics, electrode potentials and solubilities) is facilitated by density functional theory (DFT) calculations. Based upon the results, this paper proposes 1, 3-cyclohexanedione (1, 3-dione) and 1, 2-benzoquinone-4, 5-disulfonic acid (1, 2-BQDS), which are highly soluble and exhibit the most negative (~−0.2 V vs . Standard Hydrogen Electrode (SHE)) and the most positive (~0.80 V vs . Standard Hydrogen Electrode (SHE)) electrode potentials, respectively, under acidic conditions, for which the formation of short-lived and unstable radicals is avoided. The proposed molecules involve at least two proton–two-electron-transfers (pH ≤ 2.5) and yields one of the highest cell voltage (ca. 0.9 V) and reasonable energy efficiencies (>70% at 20 mA cm −2 ) in acidic electrolytes reported to date.